Negative electrode and secondary battery
By adopting a double-layer negative electrode active material layer on the negative electrode of the secondary battery, using isostatically treated natural graphite and artificial graphite in the form of secondary particles/single particles, the problem of insufficient adhesion and expansion performance of existing batteries is solved, and more efficient battery performance and longer life are achieved.
Patent Information
- Application Number
- CN202380062336.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-10-10
- Filing Date
- 2023-10-12
- Publication Date
- 2025-04-11
AI Technical Summary
The adhesion and expansion performance of existing secondary batteries are insufficient, which affects the performance and life of the battery.
The structure is adopted as a double-layer negative electrode active material layer, wherein the first layer contains natural graphite which is treated isostatically and the second layer contains artificial graphite in the form of secondary particles and artificial graphite in the form of single particles.
Improves the adhesion and expansion performance of the electrodes, achieving faster charging and longer battery life.
Smart Images

Figure BDA0005287626990000141
Abstract
Description
[Technical field]
[0001] This application claims priority to and the benefit of Korean Patent Application No. 10-2022-0132407 filed in the Korean Intellectual Property Office on October 14, 2022, and Korean Patent Application No. 10-2023-0133971 filed in the Korean Intellectual Property Office on October 10, 2023, the entire contents of which are incorporated herein by reference.
[0002] The present invention relates to a negative electrode for a secondary battery and a secondary battery including the negative electrode. [Background Technology]
[0003] Secondary batteries are commonly used not only in portable devices but also in electric vehicles (EVs) and hybrid electric vehicles (HEVs) driven by an electric driving source.
[0004] Secondary batteries have attracted attention as a new energy source that improves environmental friendliness and energy efficiency due to their major advantages of being able to significantly reduce the use of fossil fuels and using energy without generating byproducts.
[0005] Generally, a secondary battery includes a positive electrode, a negative electrode, a separator and an electrolyte interposed between the positive electrode and the negative electrode, etc. In addition, electrodes such as the positive electrode and the negative electrode may be provided with an electrode active material layer on a current collector.
[0006] As the use of secondary batteries increases, a variety of battery performance is required. In order to improve battery performance, attempts have been made to add additives to the active material layer. Depending on the type of additive, some performance of the battery may be improved, but some performance may be deteriorated. Therefore, it is necessary to study the selection or combination of materials contained in the electrode that can improve the performance required for the secondary battery. [Summary of the invention]
[0007] [Technical issues]
[0008] The present invention has been made in an effort to provide a negative electrode for a secondary battery having improved adhesion and swelling properties, and a secondary battery including the same.
[0009] [Technical solution]
[0010] An exemplary embodiment of the present invention provides a negative electrode for a secondary battery, comprising: a collector; a first negative electrode active material layer disposed on the collector; and a second negative electrode active material layer disposed on the first negative electrode active material layer, wherein the first negative electrode active material layer comprises natural graphite subjected to isostatic pressing, and wherein the second negative electrode active material layer comprises artificial graphite in the form of secondary particles and artificial graphite in the form of single particles.
[0011] Another exemplary embodiment of the present invention provides a secondary battery including the negative electrode for a secondary battery according to the above exemplary embodiment, a positive electrode, and a separator.
[0012] Another exemplary embodiment of the present invention provides a method for manufacturing a negative electrode for a secondary battery, the method comprising: forming a first negative electrode active material layer on a current collector; and forming a second negative electrode active material layer on the first negative electrode active material layer, wherein the first negative electrode active material layer comprises natural graphite subjected to isostatic pressing or a BET specific surface area of 1 m 2 / g to 3m 2 / g of natural graphite, and wherein the second negative electrode active material layer contains artificial graphite in the form of secondary particles and artificial graphite in the form of single particles.
[0013] [Beneficial Effects]
[0014] According to the negative electrode of the present invention, artificial graphite in the form of secondary particles, natural graphite treated by isostatic pressing, and artificial graphite in the form of single particles are used for the negative electrode active material layer, whereby the orientation degree in the electrode is relatively low, and the side reaction with the electrolyte is reduced, so that the expansion performance of the electrode can be improved. In addition, the natural graphite treated by isostatic pressing is formed at the lower part of the negative electrode active material layer, thereby maximizing the adhesion of the negative electrode active material layer and achieving an improved fast charging effect. [Specific implementation method]
[0015] Hereinafter, the present invention will be described in more detail to better understand the present invention. The present invention can be implemented in various forms and is not limited to the exemplary embodiments described herein. The terms or words used throughout the specification and claims should not be interpreted as limited to their conventional meanings or dictionary meanings, but should be interpreted as having meanings and concepts consistent with the technical ideas of the present invention based on the principle that the inventor can appropriately define the concepts of the words or terms in order to best illustrate his invention.
[0016] It will be further understood that when used in this specification, the terms "comprises", "includes" or "has" specify the presence of stated features, numbers, steps, constituent elements and / or combinations thereof, but do not exclude the presence or addition of one or more other features, numbers, steps, constituent elements and / or combinations thereof.
[0017] Furthermore, it will be understood that when an element such as a layer is referred to as being "on" another element, it can be "directly on" the other element, or intervening elements may be present. Conversely, when an element is referred to as being "directly on" another element, there are no intervening elements. Furthermore, when an element is referred to as being "on" a reference portion, the element is located above or below the reference portion, which does not necessarily mean that the element is located "above" or "on" in the opposite direction of gravity.
[0018] In this specification, the term "particle size" refers to the average particle size expressed as D50. D50 can be defined as the particle size at 50% of the particle size distribution, which can be measured using a laser diffraction method. For example, a method for measuring the average particle size (D50) of a positive electrode active material may include dispersing particles of the positive electrode active material in a dispersion medium, introducing the dispersion into a commercially available laser diffraction particle size measuring device (e.g., Microtrac MT 3000), irradiating the dispersion with an ultrasonic wave of about 28 kHz with an output power of 60 W, and then calculating the average particle size (D50) corresponding to 50% of the cumulative volume in the measuring device.
[0019] In the present specification, description referring only to “active material layer” without the first and second expressions may be applicable to both the first and second active material layers.
[0020] A negative electrode for a secondary battery of an exemplary embodiment of the present application includes: a current collector; a first negative electrode active material layer disposed on the current collector; and a second negative electrode active material layer disposed on the first negative electrode active material layer, wherein the first negative electrode active material layer contains natural graphite subjected to isostatic pressing, and the second negative electrode active material layer contains artificial graphite in the form of secondary particles and artificial graphite in the form of single particles. In other words, the negative electrode of the secondary battery includes a double-layer negative electrode active material layer, which contains artificial graphite in the form of secondary particles, natural graphite subjected to isostatic pressing, and artificial graphite in the form of single particles, and the natural graphite subjected to isostatic pressing is arranged at the lower part of the negative electrode active material layer. As a result, a negative electrode having excellent expansion performance and adhesion can be obtained.
[0021] Another exemplary embodiment of a method for manufacturing a negative electrode for a secondary battery includes: forming a first negative electrode active material layer on a current collector; and forming a second negative electrode active material layer on the first negative electrode active material layer, wherein the first negative electrode active material layer comprises natural graphite subjected to isostatic pressing or a graphite having a BET specific surface area of 1 m 2 / g to 3m 2 / g of natural graphite, and wherein the second negative electrode active material layer contains artificial graphite in the form of secondary particles and artificial graphite in the form of single particles.
[0022] In this specification, the term "single particle" is a concept opposite to the secondary particle form formed by agglomeration of tens to hundreds of primary particles, and refers to a particle composed of 10 or less primary particles. Specifically, in the present invention, a single particle may be a single particle composed of one primary particle, or may be a particle form formed by agglomeration of multiple primary particles.
[0023] In this specification, the term "primary particle" refers to the smallest unit of a particle recognized when an active material is observed by a scanning electron microscope, and the term "secondary particle" refers to a secondary structure formed by agglomeration of tens to hundreds of primary particles.
[0024] In this specification, the term "particle" refers to a particulate matter having a micron size, and when observed under magnification, the particle can be identified as a "grain" in the form of a crystal having a size of tens of nanometers. When the grain is further magnified and observed, a separate region in the form of atoms forming a lattice structure in a predetermined direction can be identified, wherein the region is called a "crystal". The size of the particle observed by X-ray diffraction (XRD) is defined as the crystallite size. The crystallite size can be quantitatively determined according to the Scherrer formula using XRD data.
[0025] According to an exemplary embodiment of the present invention, the first negative electrode active material layer includes natural graphite that has been isostatically pressed. Natural graphite that has been isostatically pressed can be obtained by methods such as cold isostatic pressing (CIP). Specifically, spheroidized granulated particles with adjusted sizes obtained by a jet mill are filled into a mold of a cold isostatic pressing device, all sides of the mold are filled with water, and then cold isostatically pressed for 100 seconds at a molding pressure of 90Mpa. Subsequently, the spheroidized granulated particles that have been cold isostatically pressed are disintegrated. Then, 100 parts by weight of the disintegrated spheroidized granulated particles are mixed with 5 parts by weight of asphalt (solid asphalt) as a carbon coating material, and the resulting mixture is carbonized at a temperature of 1250°C for 24 hours for carbon coating to obtain natural graphite that has been isostatically pressed. However, the method for manufacturing natural graphite that has been isostatically pressed is not limited to the above description.
[0026] As described above, when a method such as cold isostatic pressing (CIP) is used to obtain isostatically pressed natural graphite, pressure can be isotropically applied to the raw material particles from all directions. Therefore, there is an advantage that the internal voids and specific surface area of the raw material particles in the spherical granulated particles are reduced.
[0027] According to an exemplary embodiment of the present invention, the first negative electrode active material layer includes natural graphite subjected to isostatic pressing, and therefore, the degree of orientation within the electrode is relatively low, and the side reaction with the electrolyte is reduced, so that the expansion performance of the electrode can be improved and the adhesion of the negative electrode active material layer is increased.
[0028] According to an exemplary embodiment of the present invention, the BET specific surface area of the natural graphite may be 1 m 2 / g to 3m 2 / g. By using natural graphite with a BET specific surface area within the above range, there is an advantage of improving battery durability. Specifically, if the BET specific surface area exceeds 3m 2 / g, the durability is reduced due to the side reaction with the electrolyte. If the BET specific surface area is less than 1m 2 / g, it is difficult to achieve such natural graphite, and natural graphite hinders electrolyte penetration. For example, the BET specific surface area can be 1.2m 2 / g to 2.8m 2 / g, 1.2m 2 / g to 2.8m 2 / g, 1.2m 2 / g to 2.6m 2 / g, or 1.4m 2 / g to 2.4m 2 / g.
[0029] In this specification, the BET specific surface area can be measured, for example, by a BET (Brunauer-Emmett-Teller) measurement method using BELSORP (BET equipment) manufactured by BEL JAPAN using an adsorbed gas such as nitrogen.
[0030] According to an exemplary embodiment of the present invention, the average particle size (D50) of the isostatically pressed natural graphite may be 6 μm to 9 μm, 7 μm to 9 μm, or 8 μm to 9 μm. By using the isostatically pressed natural graphite having an average particle size (D50) within the above range, the effects (improved expansion properties of the electrode, improved adhesion of the negative electrode active material layer) that can be obtained when the isostatically pressed natural graphite is included in the negative electrode active material layer can be maximized.
[0031] The average particle size (D50) of natural graphite subjected to isostatic pressing can be controlled by a pulverizing process using a jet mill device. Specifically, flaky graphite having an average particle size (D50) of 200 μm is prepared and pulverized by a jet mill device to adjust the size. The pulverized flaky graphite is subjected to a spheroidizing process to obtain spherical granulated particles. However, the isostatic pressing process and the method for obtaining natural graphite having an adjusted average particle size are not limited to the above description.
[0032] According to an exemplary embodiment of the present invention, the second negative active material layer includes artificial graphite in the form of secondary particles and artificial graphite in the form of single particles.
[0033] According to an exemplary embodiment of the present invention, the average particle size (D50) of the artificial graphite in the form of a single particle may be 6 μm to 9 μm, 7 μm to 9 μm, or 8 μm to 9 μm.
[0034] According to an exemplary embodiment of the present invention, the average particle size (D50) of the artificial graphite in the form of secondary particles may be 16 μm to 22 μm.
[0035] In an exemplary embodiment of the present invention, in order to obtain artificial graphite in the form of single particles and artificial graphite in the form of secondary particles with an average particle size (D50) within the above range, methods such as pulverizing using a jet mill and heat treating after pulverizing can be used. Specifically, needle coke can be pulverized by a jet mill and then sieved to obtain a powder with an adjusted size. In addition, the powder can be heat treated (graphitized) at 3,000°C for 20 hours under an inert argon (Ar) atmosphere to prepare artificial graphite primary particles (or single particles). Artificial graphite primary particles (single particles) and a binder such as petroleum asphalt can be added and heat treated at above 1,000°C for 10 hours to obtain artificial graphite secondary particles formed by agglomeration of artificial graphite primary particles.
[0036] In an exemplary embodiment of the present invention, the OI (004 / 110) of the artificial graphite in the form of a single particle is 35 or less or 25 or less.
[0037] The OI (004 / 110) of the second negative electrode active material layer is a value obtained by X-ray diffraction analysis, which can be obtained using a general method for X-ray diffraction analysis, such as JIS K 0131-1996. The OI value of the negative electrode can be expressed as C004 / C110, wherein C004 represents the characteristic diffraction peak area of the (004) crystal plane, and C110 represents the characteristic diffraction peak area of the (110) crystal plane.
[0038] The OI (004 / 110) of the artificial graphite in the form of a single particle in the second negative electrode active material layer is a value obtained by X-ray diffraction analysis, which can be obtained by a general method for X-ray diffraction analysis, for example, using a Bruker D4 Endeavor as an X-ray diffraction analyzer. In addition, the OI value of the negative electrode can be expressed as I004 / I110, wherein I004 represents the characteristic diffraction peak area of the (004) crystal plane, and I110 represents the characteristic diffraction peak area of the (110) crystal plane.
[0039] These characteristics indicate the degree of orientation of graphite crystals in the second negative electrode active material layer. That is, the larger the OI value, the higher the degree of orientation of graphite, and the smaller the OI value, the lower the degree of orientation of graphite. When the degree of orientation of graphite crystals is low, when the battery is charged, the expansion performance of the battery can be improved by causing the battery to expand in random positions rather than only in a specific direction.
[0040] According to an exemplary embodiment of the present invention, the adhesion of the first negative electrode active material layer to the collector is 18 gF / cm or more. Since the negative electrode of the present invention is formed so that the first negative electrode active material layer and the collector are in contact with each other, the adhesion of the isostatically pressed natural graphite as the material of the first negative electrode active material layer affects the adhesion of the first negative electrode active material layer to the collector.
[0041] According to an exemplary embodiment of the present invention, the adhesion of the isostatically pressed natural graphite included in the first negative active material layer is 18 gF / cm or more. The adhesion of the isostatically pressed natural graphite may be adjusted according to the particle size distribution value.
[0042] In an exemplary embodiment of the present invention, the second negative electrode active material layer may include 30 to 90 parts by weight of the artificial graphite in the form of secondary particles based on 100 parts by weight of the negative electrode active material. When the above range is satisfied, there is an advantage of improving the expansion performance and energy density of the battery.
[0043] In an exemplary embodiment of the present invention, the second negative electrode active material layer may include 10 to 30 parts by weight of the artificial graphite in the form of single particles based on 100 parts by weight of the negative electrode active material. When the above range is satisfied, there is an advantage of improving the expansion performance and energy density of the battery.
[0044] According to an exemplary embodiment of the present specification, each negative electrode active material layer (first negative electrode active material layer and second negative electrode active material layer) may further contain negative electrode active materials in addition to isostatically pressed natural graphite, artificial graphite in secondary particle form, and artificial graphite in single particle form, and there is no limitation on the type of negative electrode active materials contained.
[0045] In an exemplary embodiment of the present specification, the content of the negative electrode active material in 100 parts by weight of the negative electrode active material layer can be 80 parts by weight or more and 99.9 parts by weight or less, preferably 90 parts by weight or more and 99.9 parts by weight or less, more preferably 95 parts by weight or more and 99.9 parts by weight or less, and most preferably 98 parts by weight or more and 99.9 parts by weight or less.
[0046] According to another exemplary embodiment of the present specification, the first negative electrode active material layer may include a negative electrode binder in addition to isostatically pressed natural graphite, and the second negative electrode active material layer may include a negative electrode binder in addition to secondary particle-form artificial graphite and single particle-form artificial graphite.
[0047] The negative electrode binder can be used to improve the adhesion between the negative electrode active material particles and the adhesion between the negative electrode active material particles and the negative electrode collector. For the negative electrode binder, those known in the art can be used. Its non-limiting examples may include polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene propylene diene monomer rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, polyacrylic acid and hydrogen are replaced by Li, Na or Ca etc. At least one of the above-mentioned materials in the group consisting of, and their various copolymers may also be included.
[0048] The content of the negative electrode binder may be 0.1 parts by weight to 20 parts by weight, for example, preferably 0.3 parts by weight to 20 parts by weight, more preferably 0.5 parts by weight to 10 parts by weight, based on 100 parts by weight of the negative electrode active material layer.
[0049] The negative electrode active material layer may not contain a conductive material, but if necessary, it may also contain a conductive material. The conductive material contained in the negative electrode active material layer is not particularly limited as long as it has conductivity and does not cause chemical changes in the battery. For example, graphite, such as natural graphite or artificial graphite; carbon black, such as acetylene black, Ketjen black, channel black, furnace black, lamp black and thermal black; conductive fibers, such as carbon fibers and metal fibers; conductive tubes, such as carbon nanotubes; carbon fluorides; metal powders, such as aluminum powder and nickel powder; conductive whiskers, such as zinc oxide and potassium titanate; conductive metal oxides, such as titanium oxide; conductive materials, such as polyphenylene derivatives, etc. Based on 100 parts by weight of the negative electrode active material layer, the content of the conductive material in the negative electrode active material layer may be 0.01 parts by weight to 20 parts by weight, preferably 0.03 parts by weight to 18 parts by weight.
[0050] The negative electrode active material layer may further include a thickener such as sodium carboxymethyl cellulose (Na-CMC), lithium carboxymethyl cellulose (Li-CMC), and cellulose nanofiber (CNF).
[0051] In an exemplary embodiment of the present specification, the thickness of each of the first and second negative electrode active material layers may be 5 μm or more and 500 μm or less.
[0052] According to an exemplary embodiment of the present specification, a thickness ratio of the first and second negative electrode active material layers (thickness of the first negative electrode active material layer:thickness of the second negative electrode active material layer) may be 3:7 to 5:5.
[0053] In an exemplary embodiment of the present specification, the negative electrode collector is not particularly limited as long as it has conductivity and does not cause chemical changes in the battery. For example, for the collector, copper, stainless steel, aluminum, nickel, titanium, sintered carbon, aluminum or stainless steel each surface-treated with carbon, nickel, titanium or silver, etc. can be used. Specifically, transition metals such as copper and nickel that adsorb carbon well can be used for the collector. The thickness of the collector can be 1 μm to 500 μm. However, the thickness of the collector is not limited thereto.
[0054] One other exemplary embodiment of the present specification provides a secondary battery including the negative electrode of the above exemplary embodiment, a positive electrode, and a separator.
[0055] In an exemplary embodiment of the present specification, the positive electrode may include a positive electrode collector and a positive electrode active material layer formed on the positive electrode collector and including a positive electrode active material. The thickness of the positive electrode active material layer may be 20 μm or more and 500 μm or less.
[0056] There is no particular limitation on the positive electrode collector, as long as it has conductivity and does not cause chemical changes in the battery. For example, stainless steel, aluminum, nickel, titanium, sintered carbon, aluminum or stainless steel with carbon, nickel, titanium or silver etc. treated on the surface, etc., can be used. In addition, the thickness of the positive electrode collector can generally be 1 μm to 500 μm, and the surface of the collector can be formed with fine concavoconvex to enhance the adhesion of the positive electrode active material. For example, the positive electrode collector can be used in various forms, such as films, sheets, foils, nets, porous bodies, foams and non-woven fabrics.
[0057] In an exemplary embodiment of the present specification, the positive electrode may include a lithium composite transition metal compound containing nickel (Ni) and cobalt (Co) as an active material. The lithium composite transition metal compound may further include at least one of manganese and aluminum. The lithium composite transition metal compound may include 80 mol% or more, for example, 80 mol% or more and less than 100 mol% of nickel in a metal other than lithium.
[0058] In an exemplary embodiment, the content of the positive electrode active material in 100 parts by weight of the positive electrode active material layer may be 80 parts by weight or more and 99.9 parts by weight or less, preferably 90 parts by weight or more and 99.9 parts by weight or less, more preferably 95 parts by weight or more and 99.9 parts by weight or less, and most preferably 98 parts by weight or more and 99.9 parts by weight or less.
[0059] According to another exemplary embodiment of the present specification, the positive electrode active material layer of the above exemplary embodiment may further include a positive electrode binder and a conductive material.
[0060] The positive electrode binder can be used to improve the adhesion between the positive electrode active material particles and the adhesion between the positive electrode active material particles and the positive electrode collector. For the positive electrode binder, those known in the art can be used. Its non-limiting examples can include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene monomer rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, their various copolymers, etc., any one or a mixture of two or more thereof can be used.
[0061] The content of the positive electrode binder may be 0.1 parts by weight to 50 parts by weight, for example, preferably 0.3 parts by weight to 35 parts by weight, more preferably 0.5 parts by weight to 20 parts by weight, based on 100 parts by weight of the positive electrode active material layer.
[0062] The conductive material contained in the positive electrode active material layer is used to impart conductivity to the electrode, and can be used without particular limitation, as long as the conductive material has electronic conductivity without causing chemical changes in the battery. Specific examples may include: graphite, such as natural graphite and artificial graphite; carbon materials, such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powder or metal fiber, such as copper, nickel, aluminum, and silver; conductive whiskers, such as zinc oxide and potassium titanate; conductive metal oxides, such as titanium oxide; or conductive polymers, such as polyphenylene derivatives, etc., any one of which or a mixture of two or more thereof can be used.
[0063] Specifically, in an exemplary embodiment, the conductive material may include one or more of single-walled carbon nanotubes (SWCNT) and multi-walled carbon nanotubes (MWCNT). Based on 100 parts by weight of the composition for the positive electrode active material layer, the content of the conductive material may be 0.1 parts by weight or more and 2 parts by weight or less, for example, preferably 0.3 parts by weight or more and 1.5 parts by weight or less, and more preferably 0.5 parts by weight or more and 1.2 parts by weight or less.
[0064] In addition to using the above-mentioned positive and negative electrode active materials, the positive and negative electrodes can be manufactured according to conventional methods for manufacturing positive and negative electrodes. Specifically, the electrode can be manufactured by applying a composition for forming an active material layer comprising the above-mentioned active materials and optional binders and conductive materials to a current collector, followed by drying and rolling. In this case, the types and contents of the positive and negative electrode active materials, binders and conductive materials are as described above.
[0065] The active material layer forming composition may further include a solvent. Specifically, the solvent may be a commonly used solvent in the art, such as dimethyl sulfoxide (DMSO), isopropanol, N-methylpyrrolidone (NMP), acetone or water, any one of which or a mixture of two or more thereof may be used. If the solvent can dissolve or disperse active materials, conductive materials and adhesives in consideration of the coating thickness and manufacturing yield of the slurry, and then achieves a viscosity that can show excellent thickness uniformity when applied to manufacture the positive and negative electrodes, the amount of solvent is sufficient. Alternatively, the positive and negative electrodes may be manufactured by casting the active material layer forming composition on another support, peeling off the film obtained from the support and stacking it on the collector.
[0066] Another exemplary embodiment of the present specification provides a method for manufacturing the negative electrode for a secondary battery of the above exemplary embodiment.
[0067] The manufacturing method is a method for manufacturing a negative electrode for a secondary battery, comprising the following steps: forming a first negative electrode active material layer on a current collector; and forming a second negative electrode active material layer on the first negative electrode active material layer, wherein the first negative electrode active material layer may include natural graphite subjected to isostatic pressing or graphite having a BET specific surface area of 1 m 2 / g to 3m 2 / g of natural graphite, and wherein the second negative electrode active material layer may contain artificial graphite in the form of secondary particles and artificial graphite in the form of single particles.
[0068] A secondary battery according to an exemplary embodiment of the present invention includes an assembly including a positive electrode, a negative electrode, a separator, and an electrolyte, and may be a lithium secondary battery.
[0069] The separator is used to separate the negative electrode from the positive electrode and provide a path for the movement of lithium ions, wherein any separator can be used as a separator without particular limitation, as long as it is commonly used in lithium secondary batteries, in particular, it is preferred to use a separator having high moisture retention capacity for the electrolyte and low resistance to the migration of electrolyte ions. Specifically, a porous polymer film can be used, for example, a porous polymer film made of a polyolefin polymer (such as ethylene homopolymer, propylene homopolymer, ethylene / butene copolymer, ethylene / hexene copolymer and ethylene / methacrylate copolymer), or a laminated structure of more than two layers thereof can be used. In addition, a common porous nonwoven fabric can be used, for example, a nonwoven fabric formed by high melting point glass fiber or polyethylene terephthalate fiber, etc. In addition, a coated separator comprising a ceramic component or a polymer material can be used to ensure heat resistance or mechanical strength, and a separator with a monolayer or multilayer structure can be selectively used.
[0070] Examples of the electrolyte may include an organic liquid electrolyte, an inorganic liquid electrolyte, a solid polymer electrolyte, a gel-type polymer electrolyte, a solid inorganic electrolyte, or a molten-type inorganic electrolyte that may be used in the manufacture of a lithium secondary battery, but are not limited thereto.
[0071] Specifically, the electrolyte may include a non-aqueous organic solvent and a metal salt.
[0072] As the non-aqueous organic solvent, for example, an aprotic organic solvent such as N-methyl-2-pyrrolidone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, triester phosphate, trimethoxymethane, dioxolane derivatives, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate or ethyl propionate can be used.
[0073] Particularly, in carbonate organic solvents, ethylene carbonate and propylene carbonate as cyclic carbonate are high viscosity organic solvents, because they have high dielectric constant, can dissociate lithium salts well, therefore can preferably use.When cyclic carbonate is mixed with the straight-chain carbonate (for example dimethyl carbonate and diethyl carbonate) with low viscosity and low dielectric constant with appropriate ratio, can prepare the electrolyte with high conductivity, therefore can more preferably use.
[0074] Lithium salts can be used as the metal salts. Lithium salts are materials that are easily soluble in non-aqueous electrolytes. For example, lithium salts selected from F - , Cl - ,I - 、NO3 - 、N(CN)2 - 、BF4 - 、ClO4 - 、PF6-、(CF3)2PF4 - 、(CF3)3PF3 - 、(CF3)4PF2 - 、(CF3)5PF - 、(CF3)6P - CF3SO3 - CF3CF2SO3 - 、(CF3SO2)2N - 、(FSO2)2N - CF3CF2(CF3)2CO - 、(CF3SO2)2CH -、(SF5)3C - 、(CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2 - 、CH3CO2 - 、SCN - and (CF3CF2SO2)2N - One or more of the group consisting of is used as anion of the lithium salt.
[0075] In addition to the above-mentioned electrolyte components, the electrolyte may further contain one or more additives, such as halogenated alkylene carbonate compounds (such as difluoroethylene carbonate, etc.), pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glycol ether, hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidinones, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol or aluminum chloride, to improve the life characteristics of the battery, inhibit the reduction of the battery capacity, and improve the discharge capacity of the battery.
[0076] Another exemplary embodiment of the present invention provides a battery module including the above-mentioned secondary battery as a unit cell and a battery pack including the battery module. Since the battery module and the battery pack include secondary batteries with high capacity, high rate capability and high cycle characteristics, the battery module and the battery pack can be used as a power source for medium and large-sized equipment selected from the group consisting of electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and power storage systems.
[0077] Since the secondary battery of the exemplary embodiment of the present invention stably exhibits excellent discharge capacity, output characteristics and cycle performance, the secondary battery can be used as a power source for the following devices: portable devices such as mobile phones, notebook computers and digital cameras, and medium and large devices selected from the group consisting of electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles and power storage systems. For example, the battery module or battery pack can be used as a power source for any one or more of the following medium and large devices: power tools; electric vehicles, including electric vehicles (EVs), hybrid electric vehicles and plug-in hybrid electric vehicles (PHEVs); or power storage systems.
[0078] Example
[0079] Hereinafter, preferred embodiments will be provided to better understand the present invention. It will be apparent to those skilled in the art that these embodiments are provided only to illustrate the present invention, and various modifications and changes may be made within the scope and technical spirit of the present invention. Such modifications and changes are naturally within the scope of the appended claims herein.
[0080] Example 1
[0081] The first negative electrode slurry was prepared in the following manner: natural graphite (adhesion: 19 gF / cm) with an average particle size (D50) of 9 μm and isostatically pressed at a pressure of 80 MPa, SBR as a binder, CMC as a thickener, and carbon black as a conductive material were added to a weight ratio of 96:1:2:1 (natural graphite: SBR: CMC: carbon black), distilled water was added, and mixed. Next, a second negative electrode slurry was prepared by measuring artificial graphite in the form of secondary particles with an average particle size (D50) of 18 μm as a negative electrode active material and artificial graphite in the form of single particles with an average particle size (D50) of 8.5 μm (OI (004 / 110): 25), SBR as a binder, CMC as a thickener, and carbon black as a conductive material to a weight ratio of 95:1:3:1 (artificial graphite (secondary particle artificial graphite: single particle artificial graphite = 80:20): SBR: CMC: carbon black), adding distilled water, and mixing. The prepared first negative electrode slurry was coated on a copper foil electrode collector to form a first negative electrode active material layer, and the prepared second negative electrode slurry was coated on the surface of the first negative electrode active material layer to form a second negative electrode active material layer, thereby preparing a negative electrode. In this case, the weight ratio of natural graphite contained in the first negative electrode active material layer to the artificial graphite contained in the second negative electrode active material layer (natural graphite: artificial graphite) is 30:70, and the weight ratio of artificial graphite in the form of secondary particles to artificial graphite in the form of single particles (secondary particles: single particles) is 80:20.
[0082] Example 2
[0083] A negative electrode was prepared in the same manner as in Example 1, except that isostatically pressed natural graphite having an average particle size (D50) of 9 μm and an adhesive force of 22 gF / cm was used.
[0084] Example 3
[0085] A negative electrode was prepared in the same manner as in Example 1, except that natural graphite subjected to isostatic pressing at a pressure of 90 MPa was used.
[0086] Example 4
[0087] A negative electrode was prepared in the same manner as in Example 1, except that a negative electrode active material having a mixing ratio of secondary particle artificial graphite and single particle artificial graphite of 70:30 was used as the negative electrode active material of the second negative electrode slurry.
[0088] Comparative Example 1
[0089] A negative electrode was prepared in the same manner as in Example 1, except that only a negative electrode active material layer including artificial graphite in the form of secondary particles having a particle size (D50) of 18 μm was formed as the negative electrode active material layer.
[0090] Comparative Example 2
[0091] A negative electrode was prepared in the same manner as in Example 1, except that a single-layer negative electrode active material layer containing (mixed) artificial graphite in the form of secondary particles with a particle size (D50) of 18 μm and artificial graphite in the form of single particles with a particle size (D50) of 18 μm was formed as the negative electrode active material layer.
[0092] Comparative Example 3
[0093] A negative electrode was prepared in the same manner as in Example 1, except that a single-layer negative electrode active material layer was formed containing (mixed) artificial graphite in the form of secondary particles with a particle size (D50) of 18 μm and natural graphite with a particle size (D50) of 9 μm that had not been isostatically pressed as the negative electrode active material layer.
[0094] Comparative Example 4
[0095] The negative electrode was prepared in the same manner as in Example 1, except that a first negative electrode active material layer comprising natural graphite having a particle size (D50) of 9 μm that had not been isostatically pressed and a second negative electrode active material layer comprising artificial graphite in the form of secondary particles having a particle size (D50) of 18 μm were formed as the negative electrode active material layers.
[0096] Comparative Example 5
[0097] The negative electrode is prepared in the same manner as in Example 1, except that a single-layer negative electrode active material layer is formed as the negative electrode active material layer, comprising (mixed) natural graphite with a particle size (D50) of 9 μm that has not been isostatically pressed, artificial graphite in the form of secondary particles with a particle size (D50) of 18 μm, and artificial graphite in the form of single particles with a particle size (D50) of 9 μm.
[0098] Comparative Example 6
[0099] A negative electrode was prepared in the same manner as in Example 1, except that a single-layer negative electrode active material layer containing (mixed) artificial graphite in the form of secondary particles with a particle size (D50) of 18 μm and artificial graphite in the form of single particles with a particle size (D50) of 9 μm was formed as the negative electrode active material layer.
[0100] Comparative Example 7
[0101] A negative electrode was prepared in the same manner as in Example 1 except that the second negative electrode slurry was coated on the surface of the copper foil electrode collector to form a second negative electrode active material layer and the first negative electrode slurry was coated on the surface of the second negative electrode active material layer to form a first negative electrode active material layer.
[0102] Adhesion between the negative electrode active material layer and the current collector of the prepared negative electrode and cycle expansion performance of batteries prepared using the negative electrodes prepared in Examples and Comparative Examples were measured and are shown in Table 1 below.
[0103] (1) Method for measuring adhesion (gF / cm) of negative electrode active material layer: Each negative electrode prepared in the examples and comparative examples was rolled and then dried in a vacuum oven at 130°C for 8 hours. Then, the negative electrode was punched into a predetermined size and fixed to the center of a glass slide with tape. Then, the peel strength was measured using a UTM (universal testing machine) while peeling the negative electrode collector.
[0104] (2) Measurement method of cycle expansion performance (expansion rate (%) @ 30 cycles (charging)): A positive electrode slurry was prepared by mixing LiCoO2 as a positive electrode active material, Li-435 (manufactured by Denka) as a conductive material, a binder and a thickener in a weight ratio of 96:2:2 (positive electrode active material: conductive material: binder + thickener), and adding N-methylpyrrolidone (NMP) as a solvent. The positive electrode slurry was applied to an aluminum foil, vacuum dried at about 130° C. for 8 hours, and rolled to prepare a sheet with an area of 1.7671 cm 2 In this case, the positive electrode is prepared so that the loading capacity of the positive electrode is about 3.4 mAh / cm 2 . A full-cell secondary battery using the negative electrodes of the embodiments and comparative examples was prepared by inserting a polyethylene separator between each negative electrode prepared in the embodiments and comparative examples and the positive electrode prepared above, and then injecting an electrolyte. As the electrolyte, an electrolyte obtained by adding vinylene carbonate (VC) to 0.5 wt % and dissolving LiPF6 to a concentration of 1 M in a non-aqueous electrolyte solvent in which ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were mixed in a volume ratio of 1:4 was used. The coin-type full-cell battery was charged and discharged in a charging range of SOC 0 to SOC 95, with the first cycle at 0.1C, the second cycle at 0.2C, and the third to 30th cycles at 0.5C. Thereafter, the expansion rate was measured according to the following mathematical formula 1.
[0105] [Mathematical formula 1]
[0106] Expansion rate (%) = {(t2-t1) / t1}×100
[0107] (t1 is the thickness of the negative electrode for the secondary battery before the first charge and discharge cycle, and t2 is the thickness of the negative electrode for the secondary battery after the 30th charge and discharge cycle.)
[0108] [Table 1]
[0109]
[0110] As shown in Table 1, it can be confirmed that the adhesion and cycle expansion performance of the negative electrode active material layer of the batteries of Examples 1 to 4 are better than those of the negative electrode active material layer of the batteries of Comparative Examples 1 to 7.
Claims
1. A negative electrode for a secondary battery, comprising: Current collector; a first negative electrode active material layer disposed on the current collector; as well as a second negative electrode active material layer disposed on the first negative electrode active material layer, The first negative electrode active material layer comprises natural graphite subjected to isostatic pressing, and The second negative electrode active material layer includes artificial graphite in the form of secondary particles and artificial graphite in the form of single particles.
2. The negative electrode for a secondary battery according to claim 1, wherein The BET specific surface area of the natural graphite is 1 m 2 / g to 3m 2 / g.
3. The negative electrode for a secondary battery according to claim 1, wherein The average particle size (D50) of the natural graphite is 6 μm to 9 μm.
4. The negative electrode for a secondary battery according to claim 1, wherein The average particle size (D50) of the artificial graphite in the form of single particles is 6 μm to 9 μm.
5. The negative electrode for a secondary battery according to claim 1, wherein The OI (004 / 110) of the artificial graphite in the form of single particles is 35 or less.
6. The negative electrode for a secondary battery according to claim 1, wherein The adhesion of the first negative electrode active material layer to the current collector is 18 gF / cm or more.
7. The negative electrode for a secondary battery according to claim 1, wherein The second negative electrode active material layer includes 30 to 90 parts by weight of the artificial graphite in the form of secondary particles based on 100 parts by weight of the negative electrode active material.
8. The negative electrode for a secondary battery according to claim 1, wherein The second negative electrode active material layer includes 10 to 30 parts by weight of the artificial graphite in the form of a single particle based on 100 parts by weight of the negative electrode active material.
9. A negative electrode for a secondary battery, comprising: Current collector; a first negative electrode active material layer disposed on the current collector; as well as a second negative electrode active material layer disposed on the first negative electrode active material layer, The first negative electrode active material layer comprises a BET specific surface area of 1 m 2 / g to 3m 2 / g of natural graphite, and The second negative electrode active material layer includes artificial graphite in the form of secondary particles and artificial graphite in the form of single particles. 10 . A secondary battery comprising the negative electrode according to claim 1 , a positive electrode, and a separator.
11. A method for manufacturing a negative electrode for a secondary battery, the method comprising: forming a first negative electrode active material layer on the current collector; and forming a second negative electrode active material layer on the first negative electrode active material layer, The first negative electrode active material layer comprises natural graphite subjected to isostatic pressing or graphite having a BET specific surface area of 1 m 2 / g to 3m 2 / g of natural graphite, and The second negative electrode active material layer includes artificial graphite in the form of secondary particles and artificial graphite in the form of single particles.
Citation Information
Patent Citations
METHOD OF AMINO ACID CODING GENE WHICH CAN BE OVEREXPRESSED IN E.coli, COMPOSITION FOR PREPARING HA OF LPAIV H9N2 RECOMBINANT VIRU, LPAIV H9N2 RECOMBINANT VIRU AND VACCINE COMPOSITION COMPRISING THE SAME
KR1020220132407A
Method for adjusting a computer-implemented fastener setting tool
KR1020230133971A